An analysis of spatial pricing and renewable generation in the British electricity system. (14th January 2008) - Di Castelnuovo, Matteo; Leach, Matthew; Pearson, Peter
This paper investigates the importance of implementing adequate locational signals and their possible effects on the development of renewable energy sources. In particular, the paper investigates a potential conflict in the British electricity system between the introduction of more efficient spatial pricing and the development of wind energy in the north of the country. The regulatory and commercial frameworks of the British electricity market are analysed against the background of locational signals and renewable energy sources. This paper suggests that in theory there is no conflict between locational signals and renewable energy, since locational signals are intended to make the electricity market more efficient, irrespective of what happens to a particular technology. However, in practice locational signals are being seen as a threat to the development of wind farms, because of political pressures and some issues of inadequacy surrounding the main transmission model. Further research is needed before the suggested alternative of locational 'discounts' for renewable energy sources is pursued by the regulator.